PELPIII: the class III pistil‐specific extensin‐like Nicotiana tabacum proteins are essential for interspecific incompatibility. (4th April 2013) - Eberle, Carrie A.; Anderson, Neil O.; Clasen, Benjamin M.; Hegeman, Adrian D.; Smith, Alan G.
Summary Pre‐zygotic interspecific incompatibility (II) involves an active inhibition mechanism between the pollen of one species and the pistil of another. As a barrier to fertilization, II effectively prevents hybridization and maintains species identity. Transgenic ablation of the mature transmitting tract (TT) in Nicotiana tabacum resulted in the loss of inhibition of pollen tube growth in Nicotiana obtusifolia (synonym Nicotiana trigonophylla) and Nicotiana repanda. The role of the TT in the II interaction between N. tabacum and N. obtusifolia was characterized by evaluating N. obtusifolia pollen tube growth in normal and TT‐ablated N. tabacum styles at various post‐pollination times and developmental stages. The II activity of the TT slowed and then arrested N. obtusifolia pollen tube growth, and was developmentally synchronized. We hypothesize that proteins produced by the mature TT and secreted into the extracellular matrix inhibit interspecific pollen tubes. When extracts from the mature TT of N. tabacum were injected into the TT‐ablated style prior to pollination, the growth of incompatible pollen tubes of N. obtusifolia and N. repanda was inhibited. The class III pistil‐specific extensin‐like protein (PELPIII) was consistently associated with specific inhibition of pollen tubes, and its requirement for II was confirmed through use of plants with antisense suppression of PELPIII. Inhibition of N. obtusifolia and N. repanda pollen tube growth required accumulation of PELPIII in the TT of N. tabacum, supporting PELPIII function in pre‐zygotic II.